David against Goliath: The diplomatic management of Venice and Florence in their conflicts with Castile (14th and 15th centuries) (Edad Media. Revista de Historia, 2024)
Diplomatic relations among Florence, Venice and Castile in the Late Middle Ages were not permanent, but rather determined by the need of Italian powers to look after their interests when damaged in Castilian territory. The present paper addresses the strategies deployed by both Italian signorie in a disadvantageous territory from a comparative perspective, to establish analogies and differences, as well as the Castilian response to their demands.
Keywords: Venice; Florence; Castile; Diplomacy; Conflict